2008
DOI: 10.1037/0012-1649.44.3.655
|View full text |Cite
|
Sign up to set email alerts
|

Online communication, compulsive internet use, and psychosocial well-being among adolescents: A longitudinal study.

Abstract: The present study investigated the relationships between adolescents' online communication and compulsive Internet use, depression, and loneliness. The study had a 2-wave longitudinal design with an interval of 6 months. The sample consisted of 663 students, 318 male and 345 female, ages 12 to 15 years. Questionnaires were administered in a classroom setting. The results showed that instant messenger use and chatting in chat rooms were positively related to compulsive Internet use 6 months later. Moreover, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
247
2
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(279 citation statements)
references
References 52 publications
18
247
2
12
Order By: Relevance
“…Several studies have provided preliminary empirical support for the basic assumptions of this model. Recent studies have produced empirical evidence supporting the claim that compulsive use is a central component of PIU (e.g., Caplan, 2005;Kim et al, 2009;van den Eijnden, Meerkerk, Vermulst, Spijkerman, & Engels, 2008). POSI has been found to be predictive of this compulsive use (Caplan, 2010;Fioravanti, Dèttore, & Casale, 2012) and mood regulation was a significant cognitive predictor of negative outcomes associated with Internet use (Caplan, 2002;Gámez-Guadix, Villa-George, & Calvete, 2012).…”
Section: The Update Model Of Generalized Problematic Internet Usementioning
confidence: 99%
“…Several studies have provided preliminary empirical support for the basic assumptions of this model. Recent studies have produced empirical evidence supporting the claim that compulsive use is a central component of PIU (e.g., Caplan, 2005;Kim et al, 2009;van den Eijnden, Meerkerk, Vermulst, Spijkerman, & Engels, 2008). POSI has been found to be predictive of this compulsive use (Caplan, 2010;Fioravanti, Dèttore, & Casale, 2012) and mood regulation was a significant cognitive predictor of negative outcomes associated with Internet use (Caplan, 2002;Gámez-Guadix, Villa-George, & Calvete, 2012).…”
Section: The Update Model Of Generalized Problematic Internet Usementioning
confidence: 99%
“…Internet and computer mediated interactions offer advantages for individuals with autistic traits because they enable them to interact with others in a safe and structured environment with reduced contextual, auditory, and visual cues. Despite its potential advantages, there is growing concern about excessive Internet use and its potential addictive properties, resulting in compulsive Internet use (van den Eijnden et al 2008;Caplan 2003). Given their strong attraction to electronic screen media, it seems likely that people with autistic traits are especially prone to compulsive Internet use.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the use of the Internet for communicational purposes in particular is related to compulsive Internet use (van den Eijnden et al 2008). Students who prefer online communication over face-to-face communication are especially prone to problematic Internet use (Caplan 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, excessive online gaming (Kuss & Griffiths, 2012b), excessive online gambling (Griffiths & Parke, 2010), and the use of social media (van den Eijnden, Meerkerk, Vermulst, Spijkerman, & Engels, 2008), such as online social networks (SNSs) (Kuss & Griffiths, 2011) appear to stand out. Their increasing diversity and usage growth among young populations (Entertainment Software Association, 2012;Lenhart, Purcell, Smith, & Zickuhr, 2012) is mirrored by the rising number of treatment studies (King, Delfabbro, Griffiths, & Gradisar, 2011;Liu, Liao, & Smith, 2012).…”
mentioning
confidence: 99%